2020
DOI: 10.1177/1010539520977304
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Livelihood Impacts of COVID-19 on Bangladeshi Lower Income People

Abstract: The objective of this research is to understand the psychological and livelihood-related impacts of coronavirus disease 2019 (COVID-19) on Bangladeshi lower income group people who depend on daily earnings for their living. Following the convenience sampling method, 576 respondents were interviewed for quantitative data and 30 in-depth interviews for qualitative information in several districts of Bangladesh. To 94.1% respondents, livelihood has been affected by the COVID-19 outbreak with an overall score of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 9 publications
5
46
0
1
Order By: Relevance
“…Informal sector workers are some of the low-income earners in Ghana (Adom et al, 2020;Danquah et al, 2020). The observation made about the impact of COVID-19 on some informal sector work supports findings from other countries suggesting that the economic well-being of low-income earning workers has been compromised during the pandemic (Jay et al, 2021;Paul et al, 2021). In Ghana, the government implemented several measures to mitigate the impact of the COVID-19 pandemic on households (Danquah et al, 2020).…”
Section: Discussionmentioning
confidence: 71%
“…Informal sector workers are some of the low-income earners in Ghana (Adom et al, 2020;Danquah et al, 2020). The observation made about the impact of COVID-19 on some informal sector work supports findings from other countries suggesting that the economic well-being of low-income earning workers has been compromised during the pandemic (Jay et al, 2021;Paul et al, 2021). In Ghana, the government implemented several measures to mitigate the impact of the COVID-19 pandemic on households (Danquah et al, 2020).…”
Section: Discussionmentioning
confidence: 71%
“…In over one year, approximately 200 million people worldwide were infected with COVID-19, of which 4.3 million have died [1]. The COVID-19 pandemic had a significant negative impact on people's socio-economic lives [2][3][4][5][6]. Various non-therapeutic measures were adopted to contain COVID-19; however, vaccines were required to control the pandemic and save lives [7].…”
Section: Introductionmentioning
confidence: 99%
“…The remaining variables contributed near about 1%, which may be considered less critical. Many earlier studies suggested staying at home and maintain social distance 6,7 to hinder community transmission. In this case, new media contributed more to creating awareness of coronavirus among the respondents.…”
Section: Predicting Contribution Of Mass Media Influences On Healthy Lifestyle Changesmentioning
confidence: 99%